Simple and cheap usability for information services - Serrano-Cobos, Jorge (Anuario ThinkEPI, 2008)
The need for real usability testing analysis is discussed, since the assumption that classical usability heuristics are not capable to cope every possible web information system use scenario. Also, a really easy and cheap way to develop real user tests based on low-fidelity protypes is explained.
Keywords: Human-Machine interaction; HCI; User centered design; Usability; Information systems design; Low-fidelity prototipes; User tests.